Exploring The Utilization Of Mathematical Concepts In The Traditional House Of Desa Beleq Sembalun - Nurhasanah, Nurhasanah; Baiq Meli Reksa Heriani ,; Rahmawati,; Lalu Ahsanul Adlani,; Andra Taufiqurrahman,; Nilza Humaira Salsabila, (Mandalika Mathematics and Educations Journal, 2023)
Culture is a community's habits that have been passed down from generation to generation and become the identity of an area. One thing that bridges education and culture, especially mathematics education, is ethnomathematics. Ethnomathematics is a science that connects cultural issues found in a tribe or region with elements of mathematics. The aim of this research is to explore the mathematical concepts contained in the traditional houses of Desa Beleq. This research is a qualitative research. The research was carried out in Sembalun Bumbung Village, Sembalun District, East Lombok Regency. The subject of this research is the informant, namely the tribal chief. Research instruments include human instruments, observation guidelines, interview guidelines and documentation. Data analysis was carried out in three stages, namely data reduction, data display and conclusion drawing. The results of this research show that building elements such as roofs, stairs, doors, walls, ornaments and other building forms of Desa Beleq traditional houses contain mathematical concepts found in geometric materials such as shapes flat, geometric shapes, and geometric transformation (reflection).